(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
Islamic feminism reveals itself as a vibrant hybrid form of activism that addresses issues of emancipation and gender equality within Arab Muslim societies by propagating the compatibility of Islam with feminist ideology. In this regard, its advocates seek to emphasize the importance of independent reasoning in offering a modern feminist-oriented reinterpretation of certain Islamic jurisprudence provisions. Despite its appeal, however, this framework has always been met with rejection and doubt from Islamists and secularists alike, both highlighting the incompatibility of Islam with feminist principles. Thus, through an exploration into the complexities of hybridity theory and the core tenets of Islamic feminism, this article aims at analyzing the realities of this framework, its perception, and the possibilities of its existence within these societies between authenticity and outlandishness. Keywords: Islamic feminism, hybridity theory, Islamic jurisprudence, feminist ideology, reinterpretation, authenticity, outlandishness